Cooperative metal–ligand influence on the formation of coordination polymers, and conducting and photophysical properties of Tl(i) β-oxodithioester complexes12. Issue 45 (6th November 2018) - Yadav, Chote Lal; Rajput, Gunjan; Manar, Krishna K.; Kumari, Kavita; Drew, Michael G. B.; Singh, Nanhai
Abstract : Eight novel luminescent and semiconducting Tl(i ) β-oxodithioester complexes forming 1D/2D coordination polymeric structures were investigated using single crystal X-ray diffraction. Abstract : Eight novel Tl(i ) β-oxodithioester complexes, [TlL] n (1–8 ), with ligands, L = methyl-3-hydroxy-3-(2-furyl)-2-propenedithioate (L1), methyl-3-hydroxy-3-(2-thienyl)-2-propenedithioate (L2), methyl-3-hydroxy-3-(3-pyridyl)-2-propenedithioate (L3), methyl-3-hydroxy-3-(4-pyridyl)-2-propenedithioate (L4), methyl-3-hydroxy-3-(9-anthracenyl)-2-propenedithioate (L5), methyl-3-hydroxy-3-(4-fluorophenyl)-2-propenedithioate (L6), methyl-3-hydroxy-3-(4-chlorophenyl)-2-propenedithioate (L7) and methyl-3-hydroxy-3-(4-bromophenyl)-2-propenedithioate (L8), were synthesized and thoroughly characterized by elemental analysis, and IR, UV-Vis, 1 H and 13 C{ 1 H} NMR spectroscopy, and their structures were ascertained by X-ray crystallography. Complexes1 and2 crystallized in P 21 and P 21 21 21 chiral space groups, respectively, and were studied using Circular Dichroism (CD) spectra. Solid state structural analyses revealed that the β-oxodithioester ligands are bonded to Tl(i ) ions in (O, S) chelating and chelating–bridging modes, thereby forming different types of 1D and 2D coordination polymeric structures. By considering the metal-assisted bonding interactions, various coordination numbers of 5–8 and 10 are established around the metal centre. Except for5 and7a which have Tl⋯Tl separations at 3.724(1) and 3.767(1), 3.891(1) Å respectively, the remaining complexes have no Tl⋯Tl distances <4.0 Å. This indicates that the majority of structures contain only weak inter- and intramolecular thallophilic interactions. The structures of1–8 highlight the role played by variations in substituents in the dithioester unit in the structure and properties of the complexes. The multi-dimensional assembly in these complexes rests on important non-covalent C–H⋯π (TlOSC3, chelate), C–H⋯X (X = F, Cl, O, N), C–H⋯π, H⋯H and rare Tl⋯H–C intermolecular anagostic interactions. The Tl⋯H–C anagostic interactions together with C–O⋯Tl and C–S⋯Tl interactions formed 7-, 11- and 12-membered chelate rings about the metal centers. The anagostic interactions in1, 2 and7b were assessed by theoretical calculations. All the complexes showed bright green luminescent emissions in solution and solid phases. Time-resolved emission spectra revealed a triexponential decay curve and short mean lifetime for fluorescence behavior.